2017
DOI: 10.3892/etm.2017.5053
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of miR‑27a suppresses the inflammatory response via the p38/MAPK pathway in intervertebral disc cells

Abstract: Abstract. The current study aimed to investigate the role of miR-27a in intervertebral disc degeneration (IDD) and to examine the underlying mechanisms. Quantitative polymerase chain reaction (qPCR) was performed to detect the expression level of miR-27a in the nucleus pulposus (NP) tissues of patients with IDD, and the results revealed an increasing expression of miR-27a in IDD compared with the control. To further investigate the role of miR-27a in IDD, a stable human NP cell line with low miR-27a expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The preliminarily screened literature was read according to the criteria of oral bioavailability (OB) ≥30% and drug-likeness (DL) ≥0. 18 component of BHD were retrieved. The targets and the effective components of BHD were then inputted into the Perl plug-ins.…”
Section: Effective Components and The Selection Of Targets Of Bhdmentioning
confidence: 99%
“…The preliminarily screened literature was read according to the criteria of oral bioavailability (OB) ≥30% and drug-likeness (DL) ≥0. 18 component of BHD were retrieved. The targets and the effective components of BHD were then inputted into the Perl plug-ins.…”
Section: Effective Components and The Selection Of Targets Of Bhdmentioning
confidence: 99%
“…Novel research has shown that miR-27a promotes ERK phosphorylation by downregulation of the ERK inhibitor sprouty2 (50). It has also been proven that miR-27a regulates the p38/mitogen-activated protein kinase (MAPK) signaling pathway (51). Furthermore, miR-27a directly silences the FBXW7 gene by binding to its 3′ untranslated region (UTR), thereby reducing the expression of FBXW7 in cancer cell.…”
Section: Roles Of Mir-27a In Regulating Signaling Pathwaysmentioning
confidence: 99%
“…The current study tested the hypothesis that MetS modulates in MetS-MSCs the content of miRNA related to senescence. For this purpose, senescence biomarkers were evaluated and MSC miRNA expression characterized using high-throughput RNA sequencing analysis, as well as selective inhibition of miR-27b, a MAPK regulator 14 , which was found to be elevated in MetS-MSCs. Importantly, we characterize the miRNA spectrum that may be involved in regulation of MSC senescence in MetS.…”
Section: Introductionmentioning
confidence: 99%